Prognostic implications of pulmonary hypertension in heart failure preserved and reduced ejection fraction - Rosyidi, Muhammad Azhar; Yogibuana, Valerinna (Universitas Brawijaya, 2026)
Pulmonary hypertension (PH) attributable to left heart disease (PH associated with left heart disease, PH-LHD) is the most common type of PH. PH-LHD is an important indicator of elevated morbidity and mortality in individuals with heart failure, both heart failure with preserved and reduced ejection fraction despite receive adequate therapy. Literature was sourced from major scientific databases and studies relevant to symptoms, examinations, management, and prognostic implications of PH-LHD. Pathophysiologically, PH-LHD is a gradual process that begins with increased left-heart pressure (postcapillary component), which triggers a series of biological changes in the pulmonary vasculature (precapillary component). This process ultimately places an excessive burden on the right ventricle, resulting in right ventricular dysfunction and failure, which are the main determinants of prognosis. Symptoms of PH-LHD are usually characterized by disproportionate dyspnea that is not consistent with left ventricular ejection fraction and other comorbidities. Echocardiography can noninvasively assess the probability of pulmonary hypertension in heart failure patients. A definitive diagnosis of PH-LHD requires confirmation through right heart catheterization. The most important prognostic factors are not only determined by the degree of hemodynamic severity, but also depend heavily on the degree of right ventricular dysfunction and the status of right ventricle–pulmonary artery coupling. Management of PH-LHD is through optimization of basic Guideline-Directed Medical Therapy (GDMT) to reduce mortality and morbidity.